(untitled) (Universal International Scientific Journal, 2026)
Higher education solves such basic tasks as training highly qualified specialists,developing science, technology and culture, and promoting social development. The article, based on documentary and historiographical sources, analyzes the process of reforming higher education in China from 1992 to 2022 and the efforts of its institutions, reveals the dynamics of growth in the number of universities and the number of students, and notes the specifics and complexities of the process. The stages of higher education reform are highlighted and their content is revealed, China’s efforts to create key universities and introduce new academic disciplines (“Project 211”, “Project 985”, “Double First Class Project “ are highlighted.